Keeping secrets - Beechwood, Beth.; Disney Channel (Firm) (New York : Disney Press, 2006)
Miley Stewart tries to hide the fact that she is really pop star Hannah Montana, but keeping her secret and balancing school and friends soon threaten to ruin everything Miley has worked so hard for.
"Based on the television series, Hannah Montana, created by Michael Poryes and Rich Correll & Barry O'Brien."
"Disney Channel."
3.9
3-6
3-6
Keywords: Singers -- Fiction; Secrets -- Fiction; Singers -- Fiction; Secrets -- Fiction